3D‐Printed Franz cells – update on optimization of manufacture and evaluation. (11th June 2020) - Sil, B. C.; Belgrave, R. G.; Alvarez, M. P.; Luo, L.; Cristofoli, M.; Penny, M. R.; Moore, D. J.; Hadgraft, J.; Hilton, S. T.; Lane, M. E.
Abstract: Objectives: Laboratory in vitro permeation processes require the use of modified Franz type diffusion cells which are conventionally fabricated from glass. Fragility and high cost are frequently associated with this type of laboratory apparatus. The purpose of our present research was to develop a simple, economical and versatile approach to manufacture Franz type cells using additive manufacturing (AM). Methods: Graphical Franz diffusion cell designs were reproduced with a stereolithography (SLA) 3D printer and assessed over a minimum period of 24 h. The surface morphology of AM printouts was analysed before and after compatibility studies using scanning electron microscopy (SEM). Comparative permeation studies in both glass and AM Franz type diffusion cells were conducted using a caffeine solution (1.5 mg mL ‑1 ), applied to a model silicone membrane. Results: Testing of the 3D printed scaffolds confirmed similar recovery of the permeant when compared to glass cells: 1.49 ± 0.01 and 1.50 ± 0.01 mg mL ‑1, respectively, after 72 h. No significant differences were visible from the SEM micrographs demonstrating consistent, smooth and non‐porous surfaces of the AM Franz cells' core structure. Permeation studies using transparent 3D printed constructs resulted in 12.85 ± 0.53 µg cm ‑2 caffeine recovery in the receptor solution after 180 min with comparable permeant recovery, 11.49 ± 1.04 µg cm ‑2, for the glass homologues. Conclusion: AM constructs can be considered as viable alternatives to the use of conventional glass apparatus offering a simple, reproducible and cost‐effective method of replicating specialised laboratory glassware. A wider range of permeants will be investigated in future studies with these novel 3D printed Franz diffusion cells. Abstract : Demonstration of the practical use of additive manufacturing (AM) in a cosmetic science scenario. This study shows that stability testing and permeation studies done using 3D‐printed scaffolds rendered similar recovery of permeant (caffeine) when compared to its glass homologues. Résumé: Objectif: les processus de perméation in vitro en laboratoire nécessitent l'utilisation de cellules de diffusion de type Franz modifiées, fabriquées traditionnellement en verre. La fragilité et un coût élevé sont fréquemment associés à ce type d'appareil de laboratoire. L'objectif de nos travaux de recherche actuels était de développer une approche simple, économique et polyvalente pour fabriquer des cellules de type Franz à l'aide de la fabrication additive (FA). Méthodes: les conceptions des cellules de diffusion Franz graphiques ont été reproduites avec une imprimante 3D stéréolithographie (SLA) et évaluées sur une période minimum de 24 h. La morphologie de surface des impressions FA a été analysée avant et après des études de compatibilité à l'aide de la microscopie électronique à balayage (MEB). Des études comparatives de perméation des cellules de diffusion de type Franz en verre et FA ont été réalisées à l'aide d'une solution de caféine (1, 5 mg ml ‐1 ) appliquée à un modèle de membrane en silicone. Résultats: les tests des supports imprimés 3D ont confirmé une récupération similaire du perméant par rapport aux cellules de verre : 1, 49 ± 0, 01 et 1, 50 ± 0, 01 mg ml ‐1, respectivement, après 72 h. Aucune différence significative n'a été observée sur les micrographiques MEB, montrant des surfaces cohérentes, lisses et non poreuses de la structure centrale des cellules Franz FA. Les études de perméation utilisant des constructions transparentes imprimées en 3D ont conduit à une récupération de la caféine de 12, 85 ± 0, 53 μg cm ‐2 dans la solution de récepteur après 180 min avec une récupération de perméant comparable, 11, 49 ± 1, 04 μg cm ‐2, pour les homologues de verre. Conclusion: les constructions FA peuvent être considérées comme des alternatives viables à l'utilisation d'appareils de verre conventionnels offrant une méthode simple, reproductible et rentable de réplication de la verrerie de laboratoire spécialisée. Une gamme plus large de perméants sera étudiée dans de futures études avec ces nouvelles cellules de diffusion Franz imprimées en 3D.